EFEKTIVITAS UJIAN AKHIR SEMESTER SECARA ONLINE MENGGUNAKAN APLIKASI GOOGLE FORM PADA SMP MA'ARIF NU CIMANGGU - Setiawan, Diky; Hasymi Somaida, Mochammad (Jurnal Teknologi dan Bisnis, 2020)
The Corona virus is a virus that originates from China, and spreads rapidly throughout the world andbegan to spread to Indonesia in early March 2020. The impact of Covid-19 has caused losses in all fields,be it economy, education, etc. In the field of education, activities both learning and examinations must bereplaced online due to the impact of the spread of Covid-19. This study aims to determine theeffectiveness of the implementation of UAS which is carried out online using the Google Form applicationmedia at SMP MA'ARIF NU CIMANGGU. This research uses the quantitative survey method whichdescribes the online UAS implementation activities at SMP MA'ARIF NU CIMANGGU during thepandemic. The object consists of 35 student respondents. The data sample collection is done using aquestionnaire / questionnaire containing questions related to the implementation of UAS online using theGoogle Form application at SMP MA ' ARIF NU CIMANGGU. Based on the results of this study, theimplementation of online UAS runs effectively f and good, it can be seen from the results of satisfactorystudent scores. The application used is of course the Googke Form as the main media, and Whatsapp as amedium for interaction between teachers and students. The obstacles experienced are regarding badconnections, limited quota, schedules that frequently change, as well as difficulties in understandingsubject matter.Keywords: Covid-19,impact,effectiveness